Inflammation and stress-related candidate genes, plasma interleukin-6 levels, and longevity in older adults. - Walston, Jeremy D; Matteini, Amy M; Nievergelt, Caroline; Lange, Leslie A; Fallin, Dani M; Barzilai, Nir; Ziv, Elad; Pawlikowska, Ludmila; Kwok, Pui; Cummings, Steve R; Kooperberg, Charles; LaCroix, Andrea; et al. (Exp Gerontol, 2009)
Interleukin-6 (IL-6) is an inflammatory cytokine that influences the development of inflammatory and aging-related disorders and ultimately longevity. In order to study the influence of variants in genes that regulate inflammatory response on IL-6 levels and longevity, we screened a panel of 477 tag SNPs across 87 candidate genes in >5000 older participants from the population-based Cardiovascular Health Study (CHS). Baseline plasma IL-6 concentration was first confirmed as a strong predictor of all-cause mortality. Functional alleles of the IL6R and PARP1 genes were significantly associated with 15%-20% higher baseline IL-6 concentration per copy among CHS European-American (EA) participants (all p<10(-4)). In a case/control analysis nested within this EA cohort, the minor allele of PARP1 rs1805415 was nominally associated with decreased longevity (p=0.001), but there was no evidence of association between IL6R genotype and longevity. The PARP1 rs1805415--longevity association was subsequently replicated in one of two independent case/control studies. In a pooled analysis of all three studies, the "risk" of longevity associated with the minor allele of PARP1 rs1805415 was 0.79 (95%CI 0.62-1.02; p=0.07). These findings warrant further study of the potential role of PARP1 genotype in inflammatory and aging-related phenotypes.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Case-Control Studies; Female; Genetic Variation; Genotype; Humans; Inflammation; Interleukin-6; Longevity; Male; Phenotype; Poly (ADP-Ribose) Polymerase-1; Poly(ADP-ribose) Polymerases; Risk Factors

Heritability of and mortality prediction with a longevity phenotype: the healthy aging index. - Sanders, Jason L; Minster, Ryan L; Barmada, M Michael; Matteini, Amy M; Boudreau, Robert M; Christensen, Kaare; Mayeux, Richard; Borecki, Ingrid B; Zhang, Qunyuan; Perls, Thomas; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Longevity-associated genes may modulate risk for age-related diseases and survival. The Healthy Aging Index (HAI) may be a subphenotype of longevity, which can be constructed in many studies for genetic analysis. We investigated the HAI's association with survival in the Cardiovascular Health Study and heritability in the Long Life Family Study. METHODS: The HAI includes systolic blood pressure, pulmonary vital capacity, creatinine, fasting glucose, and Modified Mini-Mental Status Examination score, each scored 0, 1, or 2 using approximate tertiles and summed from 0 (healthy) to 10 (unhealthy). In Cardiovascular Health Study, the association with mortality and accuracy predicting death were determined with Cox proportional hazards analysis and c-statistics, respectively. In Long Life Family Study, heritability was determined with a variance component-based family analysis using a polygenic model. RESULTS: Cardiovascular Health Study participants with unhealthier index scores (7-10) had 2.62-fold (95% confidence interval: 2.22, 3.10) greater mortality than participants with healthier scores (0-2). The HAI alone predicted death moderately well (c-statistic = 0.643, 95% confidence interval: 0.626, 0.661, p < .0001) and slightly worse than age alone (c-statistic = 0.700, 95% confidence interval: 0.684, 0.717, p < .0001; p < .0001 for comparison of c-statistics). Prediction increased significantly with adjustment for demographics, health behaviors, and clinical comorbidities (c-statistic = 0.780, 95% confidence interval: 0.765, 0.794, p < .0001). In Long Life Family Study, the heritability of the HAI was 0.295 (p < .0001) overall, 0.387 (p < .0001) in probands, and 0.238 (p = .0004) in offspring. CONCLUSION: The HAI should be investigated further as a candidate phenotype for uncovering longevity-associated genes in humans.
Keywords: Aged; Aging; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotype; Health Behavior; Humans; Longevity; Male; Phenotype; Retrospective Studies; Risk Factors; Survival Rate; United States

Association of mitochondrial DNA levels with frailty and all-cause mortality. - Ashar, Foram N; Moes, Anna; Moore, Ann Z; Grove, Megan L; Chaves, Paulo H M; Coresh, Josef; Newman, Anne B; Matteini, Amy M; Bandeen-Roche, Karen; Boerwinkle, Eric; Walston, Jeremy D; Arking, Dan E (J Mol Med (Berl), 2015)
Mitochondrial function is altered with age and variants in mitochondrial DNA (mtDNA) modulate risk for several age-related disease states. However, the association of mtDNA copy number, a readily available marker which reflects mitochondrial depletion, energy reserves, and oxidative stress, on aging and mortality in the general population has not been addressed. To assess the association between mtDNA copy number and two primary outcomes--prevalent frailty and all-cause mortality--we utilize data from participants who were from two multicenter, multiethnic, community-based, prospective studies--the Cardiovascular Health Study (CHS) (1989-2006) and the Atherosclerosis Risk in Communities (ARIC) study (1987-2013). A total of 4892 participants (43.3% men) from CHS and 11,509 participants (44.9% men) from ARIC self-identifying as white or black were included in the analysis. mtDNA copy number, the trait of interest, was measured using a qPCR-based method in CHS and an array-based method in ARIC from DNA isolated from whole blood in participants from both cohorts. In race-stratified meta-analyses, we observe a significant inverse association of mtDNA copy number with age and higher mtDNA copy number in women relative to men. Lower mtDNA copy number was also significantly associated with prevalent frailty in white participants from CHS (OR 0.91, 95% CI 0.85-0.97). Additionally, mtDNA copy number was a strong independent predictor of all-cause mortality in an age- and sex-adjusted, race-stratified analysis of 16,401 participants from both cohorts with a pooled hazard ratio of 1.47 (95% CI 1.33-1.62) for the lowest quintile of mtDNA copy number relative to the highest quintile. Key messages: Mitochondrial DNA (mtDNA) copy number is associated with age and sex. Lower mtDNA copy number is also associated with prevalent frailty. mtDNA copy number is a significant predictor of all-cause mortality in a multiethnic population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; DNA, Mitochondrial; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Dosage; Geriatric Assessment; Humans; Kaplan-Meier Estimate; Male; Mortality; Odds Ratio; Population Surveillance; Prospective Studies; Surveys and Questionnaires; United States